Governança de tecnologia da informação e o compliance em instituição de serviço social autônomo - Castro, Alexandre Ramires de (Universidade do Vale do Rio dos Sinos, 2012)
Information Technology (IT) is usually recognize by technological support, is fundamental to sustain what may be unglamorous and taken-for granted business operations. Due this reason, IT must be scalable with the growth organization and offers a means for increasing productivity. However, for ensure an effective IT management becomes complex. Information Technology Governance of (ITG), proposing a structure of relationships and processes that direct and control an organization to achieve its g oal of adding value to the business by managing risk balanced with the IT return on invest ment. In IT governance, Compliance process makes the executives responsible for establ ishing, evaluating and monitoring the effectiveness of internal organizations controls. T his paper makes a survey that checks the perception about the Compliance influence on IT Governance practices. Performed in a Brazilian organizations context, called Social Autonomous Service Organizations (SSA), this kind of organization is audited and controlled by federal oversight agencies, also internal audited and controlled by an Audit Committee. This control exists due the fact of compulsory contribution collected by the federal government. This requires a completed Compliance processes for organization, including IT. Case study was a quantitative way, with a statistic population of 108 sent electronic questionnaires. Responses analyzed from 78 employees of the Regional Departments in all Brazilian country survey answered. IT governance practice most indicated, with 92% answers, choose how as the most support Compliance process in organizations was the Plan for Information Technology (PDTI). Nonparametric statistical test Kruskal-Wallis and Spearmanρ has been used to detect significant statistical diferences between groups in the sample with respect to IT Governance practices. Results lead to conclusion that there no is significant statistical evidence to accept that Compliance influence on IT Governance practices, this is a perception fo r Social Autonomous Service Organizations employees.
Keywords: Governança de tecnologia da informação; Compliance; Serviço social autônomo; Information technology governance; Social autonomous service organization; IT governance; ACCNPQ::Ciências Sociais Aplicadas::Administração